Mathematical Physics Modelling and Prediction of Oil Spill Trajectory for a Catenary Anchor Leg Mooring (CALM) System - Xuanze Ju; Zili Li; Baohui Dong; Xianwu Meng; Shuguang Huang (Advances in Mathematical Physics)
The catenary anchor leg mooring (CALM) system usually moored a heavy oil tanker; due to its complex working mechanism and special working environment, oil spill accidents are easy to happen. Once the oil spill accident happens, it not only causes huge economic loss, but also kills the marine ecological environment. Oil spill trajectory model considers almost all weathering processes including evaporation, emulsification, dispersion, dissolution, photooxidation, sedimentation, and biodegradation. Model simulations indicated that both tidal currents and wind drag force have significant effect in oil spill movement. The dominant wind in the area is South-westerly wind during the summer monsoon and North-easterly wind during the winter monsoon, but South-westerly wind is far stronger and last longer than the North-easterly wind. As a result, oil spill trajectory is most likely towards offshore to North-east during the summer period (April to September). During the winter period (November–January), oil spill would move towards shore under North-westerly winds. Once oil reaches shore, it would stay at shore permanently and eventually sink to seabed or beach in the simulation. Although the model does not consider longshore drift by waves, oil movement along shore by waves would be a slow process. Therefore, the impact of oil spill during the winter monsoon would be limited to local area around Ras Markaz.